STRATEGI GURU TAHFIDZ DALAM MENGOPTIMALKAN KEMAMPUAN MENGHAFAL Al-QUR’AN SISWA MI. MIFTAHUL ULUM - Mahmadatul Choiriyah; Luluk Zahro Maulidiya; Nisrina Huwaida; Devy Habibi Muhammad (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
This study aimed to determine the effectiveness of tahfidz teachers' strategies in optimizing the Qur'an memorization abilities of third-grade students at MI Miftahul Ulum. The research employed a Classroom Action Research (CAR) method conducted in two cycles, consisting of planning, action, observation, and reflection stages. The participants were 15 students enrolled in the Qur'an memorization program. The strategies implemented included the talaqqi method, scheduled muraja'ah, individual memorization submission, intensive mentoring, small-group learning, as well as motivation and reward systems. Data were collected through observation, interviews, memorization tests, and documentation, then analyzed quantitatively and qualitatively. The findings revealed a significant improvement in students' Qur'an memorization abilities in each cycle. The success rate increased from 52.9% in the pre-cycle stage to 70% in Cycle I and reached 92.9% in Cycle II. The improvement was reflected in students' memorization fluency, accuracy in tajwid and makharij al-huruf, muraja'ah ability, as well as motivation and discipline. Therefore, the tahfidz teachers' strategies proved effective in optimizing the Qur'an memorization abilities of third-grade students at MI Miftahul Ulum.